The influence of gender on police and professionals dealing with domestic violence and abuse in Greece and the impact on victims - Kravvariti, Vasiliki (2020)
The aim of the Thesis is to investigate the influence of gender of victims and offenders on police and professionals dealing with domestic violence and abuse (DVA) in Greece, and the impact that their responses have on victims. This aim was achieved by first conducting a systematic literature review assessing the quality of 26 quantitative papers on police responses. Four or more of the studies identified victim factors as; gender of victim female, cohabiting with an abusive partner, the severity of the injury, and victim under the influence of alcohol or drugs to be associated with the arrest of the perpetrator. Four or more of the studies identified offender factors as; gender of offender male, the severity of the incident, use of weapon and offender under the influence of alcohol or drugs to be also linked to arrest. Overall, it was observed that male offenders were arrested more often than female offenders. Women were more likely to be arrested if they were intoxicated and/or had used a weapon. Evidence from the review showed on average female victims represent 86.2% and male victims represent 17.3% of DVA incident reports to the police. Of these, 63.2% of male offenders and 11.5% of female offenders were arrested.